Analisis Rasio Likuiditas, Solvabilitas dan Rentabilitas Pada Commanditaire Vennootschap (CV) Sumber Rezeki - Erni Susanti; Wahyudi; Ika Nurhasanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Analysis of liquidity ratios shows that the company is in quite good condition in meeting its short-term obligations. With a current ratio in 2020 of 8.57 times, in 2021 of 7.41 times and in 2022 of 0.1 times. The quick ratio in 2020 was 8.57 times, in 2021 it was 7.41 times, and in 2022 it was 0.1. The cash ratio in 2020 was 822%, in 2021 it was 718%, and in 2020 it was 4%. Solvency ratio analysis shows that the company fulfills all its obligations in good condition. The Debt to Asset Ratio in 2020 was 12%, in 2021 it was 13%, and in 2022 it was 70%. Debit to Equity in 2020 is 13%, in 2021 is 15%, and in 2022 is 24%, Long Term Debt to Equity Ratio in 2020, 2021 and 2022 cannot be analyzed due to the unavailability of long-term liabilities. Profitability ratio analysis shows that the profit margin calculation results in 2020 are 11%, in 2021 they are 23%, and in 2022 they are 11%. Net Profit Margin in 2020 will be 8%, in 2021 it will be 10%, and in 2022 it will be 6%. Return on Investment in 2020 will be 15%, in 2021 it will be 29% and in 2022 it will be 31%. Return on Equity in 2020 was 17%, in 2021 it was 34%, and in 2022 it was 104%.